Intraoperative computed tomography imaging for navigated laparoscopic renal surgery: first clinical experience - Simpfendörfer, Tobias; Gasch, Claudia; Hatiboglu, Gencay; Müller, Michael; Maier-Hein, Lena; Hohenfellner, Markus; Teber, Dogu (Journal of endourology, 2016)
Introduction: Laparoscopic partial nephrectomy (LPN) remains challenging in endophytic and complex kidney tumors as the clear understanding of tumor location and spreading depends on a precise analysis of available imaging. The purpose of this study was to investigate navigated kidney surgery using intraoperative cone-beam computed tomography (CBCT) images in conjunction with a previously proposed method for augmented reality (AR) guidance for safe LPN.Materials and Methods: The concept proposed is based on using an intraoperative CBCT scan for (1) marker-based AR guidance for fast and reliable tumor access and (2) enhancement of real-time fluoroscopy images for accurate tumor resection. Workflow and accuracy of the system were assessed using a porcine kidney model. Ten patients with complex or endophytic tumor localization and R.E.N.A.L. Nephrometry Score of at least nine scheduled for LPN were included in this study. Patients received an intraoperative CBCT after marker placement. Defining the resection line was assisted by AR. In addition, fluoroscopy imaging for depth perception was used for assistance during dissection. Feasibility and performance were assessed by histopathological results, peri- and postoperative data.Results: Surgery was performed successfully and negative margins were found in all cases. Segmental branches of the renal artery shifted as much as 10 mm in the vertical and 11 mm in the sagittal axis intraoperatively compared to preoperative imaging. Fluoroscopy to intraoperative computed tomography image fusion enabled enhanced depth perception during dissection in all cases. Radiation dose area product was 4.8 mGym2.Conclusions: The application of the navigation system is feasible and allows for safe and direct access to complex or endophytic renal masses. Radiation limits the application to selected indications.